'Urf Analysis Study Of The Salenan Tradition After The Engagement - Makhtum, Maulana Mokhammad; Ni'ami, Mohammad Fauzan (Fakultas Syariah INSURI Ponorogo, 2022)
This article will discuss the salenan tradition after the engagement of the Duko Timur village community, Larangan District, Pamekasan Regency. This tradition is seen as an obligation that must be carried out by couples who have carried out an engagement. The focus of this study is to photograph the salenan tradition by tracing the people's understanding of the tradition so that the philosophical tradition of the tradition is revealed. Because of this, this article uses field research with data collection patterns in the form of observations and interviews. While this paper uses a sociological approach which will then be analyzed using the theory of Islamic law, namely Abdul Karim Zaidan's 'urf perspective. This paper finds that salenan is an 'urf shāhīh which can be used as a source of law for the surrounding community, this is found through the achievement of the requirements of a tradition that can be said to be an ‘urf shāhīh in Abdul Karim Zaidan's perspective. In addition, it was also found that the salenan tradition was included in the category of 'urf fi'lī and 'urf 'khāsh.